Converting corpses: the religious other in the Munich Oswald and St Erkenwald - Mary Boyle (Taylor and Francis, 2015)
This article investigates the concerns about the fate of non-Christians after death in the Middle High German Munich Oswald by reading it alongside the Middle English St Erkenwald. These texts ascribe to their protagonists, the Anglo-Saxon saints Erkenwald, Bishop of London and Oswald, King of Northumbria, the power to raise, convert, and baptize the dead. The article considers the possible impact on this tradition of the legend of the Emperor Trajan's post-death relief from Hell, as well as the different deployment of the posthumous conversion motif in each text: the religious other of the Munich Oswald is contemporary yet geographically distant, while the religious other of St Erkenwald is temporally distant but geographically proximate. This article considers how far the Munich Oswald and St Erkenwald share a formula for dealing with an exceptional solution to an eternal problem.